Targeting Cognitive Frailty: Clinical and Neurobiological Roadmap for a Single Complex Phenotype - Panza, Francesco; Seripa, Davide; Solfrizzi, Vincenzo; Tortelli, Rosanna; Greco, Antonio; Pilotto, Alberto; Logroscino, Giancarlo (Journal of Alzheimer's disease, 2015)
Late-life cognitive disorders may be prevented by influencing age-related conditions such as frailty, characterized by decreased resistance to stressors and increased risk for adverse health outcomes. In the present review article, we examined clinical and epidemiological studies investigating the possible role of different frailty models in modulating the risk of Alzheimer's disease (AD), dementia, vascular dementia (VaD), mild cognitive impairment (MCI), and late-life cognitive impairment/decline that have been published over the past 3 years. Both deficit accumulation and physical frailty models were associated with late-life cognitive impairment/decline, incident dementia, AD, MCI, VaD, non-AD dementias, and AD pathology, proposing cognitive frailty as a new clinical construct with coexisting physical frailty and cognitive impairment in nondemented older subjects. Two subtypes of this new clinical condition have been recently proposed: "potentially reversible" cognitive frailty and "reversible" cognitive frailty. The physical factors should be physical prefrailty and frailty, while the cognitive impairment of potentially reversible cognitive frailty should be MCI (Clinical Dementia rating Scale = 0.5), while the cognitive impairment of reversible cognitive frailty should be pre-MCI Subjective Cognitive Decline (SCD), as recently proposed by the SCD Initiative Working Group. The mechanisms underlying the cognitive-frailty link are multifactorial and vascular, inflammatory, nutritional, and metabolic influences may be of major relevance. Considering both physical frailty and cognition as a single complex phenotype may be crucial in the prevention of dementia and its subtypes with secondary preventive trials on cognitive frail older subjects.